THE IMPACT OF THE ORGANIZATION'S MANAGEMENT SYSTEM ON WORK EFFICIENCY - Azamjonovich, Usmanov Adkhamjon (Journal of Artificial Intelligence and Digital Economy, 2024)
In today's globalization process, the effective organization of each organization's management system directly depends on the factors influencing it. Since the main goal of organizational management is to achieve labor and activity efficiency, it is necessary to constantly study the factors influencing it, adapting it to the demands of the time. This article examines and analyzes the key factors related to the organization's effectiveness.